Serum adiponectin and leptin in relation to risk for preeclampsia: results from a large case-control study. - Dalamaga, Maria; Srinivas, Sindhu K; Elovitz, Michal A; Chamberland, John; Mantzoros, Christos S (Metabolism, 2011)
Conditions resulting in insulin resistance, as well as metabolic, immune, and angiogenic perturbations, have been associated with an increased risk of preeclampsia (PE). Our purpose was to assess whether the adipose tissue-secreted hormones adiponectin, which has immune-modulating, metabolic, and angiogenic properties, and leptin, which reflects overall fat mass, are associated with PE risk. We performed a case-control design study within a hospital-based cohort of 368 pregnant women (106 with PE and 262 controls; mean age, 26.6 ± 6.8 years; mean gestational age at admission, 38.2 ± 2.8 weeks) between March 2005 and August 2007 at the Hospital of Pennsylvania University. Serum adiponectin and leptin were measured by radioimmunoassay. Statistical analysis of data was performed using simple and multiple regression analyses. No significant differences in adiponectin or leptin levels between preeclamptic and control pregnant women emerged in univariate analyses (P = .57 and P = .15, respectively). Among preeclamptic women, there were also no differences in adipokines between those with mild and severe disease. Serum adiponectin and leptin were not associated with higher risk of PE before and after adjustment for maternal age, race, primigravida, smoking status, body mass index at screening, gestational age at admission, history of PE, chronic hypertension, and gestational diabetes (odds ratio, 0.93; 95% confidence interval, 0.83-1.04 and odds ratio, 1; 95% confidence interval, 0.97-1.03, respectively). Maternal serum adiponectin and leptin levels, drawn at the time of PE diagnosis, were not associated with PE.
Keywords: Adiponectin; Adult; Case-Control Studies; Cohort Studies; Female; Humans; Leptin; Pre-eclampsia; Pregnancy; Risk Factors; Severity of Illness Index; Young Adult